Ձագավանքի համալիրը և նրա վիմագրերը - Ռուբեն Գասպարյան (ՀՀ ԳԱԱ հրատ.)
Монастырь Дзагаванк – один из значительных научно-просветительских и культурных центров гавара Котайк ашхара Айрарат. Наиболее ранняя церковь монастыря – постройка характерной для VII в. архитектурной композиции, где погребены останки мученика Давида Двнеци. Dzagavank monastery is one of the famous cultural and research-educational centres. Congregation’s name is coming from the nearest Dzag settlement. The oldest church is a 7th century architectural building, with the remains of the martyr David Dvnetsi.
Keywords: History; Auxiliary Sciences of History; Inscriptions; Epigraphy; D History; N Fine Arts; NA Architecture